Alasan Penggunaan K-Pop Oleh Korea Selatan Dalam Upaya Normalisasi Dengan Korea Utara - Ananda Pinatih, Gusti Ayu Sabdhadewi; Kumala Dewi, Putu Ratih; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2019), 2020)
ABSTRACT   This study aims to explain the efforts of the South Korean Government, in normalizing diplomatic relations, with North Korea. The normalization effort was carried out through cultural performances, namely the holding of the Spring is Coming concert, which featured K-Pop musicians in North Korea on April 1 2018. Previously, the South Korean Government had used K-Pop as a propaganda broadcast against retaliatory nuclear weapons attacks carried out by North Korea. Therefore, the researcher uses the framework of post structuralism, meaning in international relations and discourse struggles, to be able to describe the direction of the use of K-Pop by South Korea. This research then produced a reason for using K-Pop as an effort to normalize, because the South Korean Government wanted to instill admiration for their culture, in North Korean society. Researchers used this type of qualitative research method, with descriptive patterns as data presentation techniques.   Keyword: Concept of Discursive Struggle, K-Pop, Normalization, Post Structuralism.